A Survey of Mechanical Ventilation Weaning Practices in ICUs of Bangladesh - Faruq, Mohammad Omar; Ahsan, ASM Areef; Fatema, Kaniz; Ahmed, Fatema; Sultana, Amina; Mallick, Uzzwal Kumar; Mohammad Asaduzzaman, -; Islam, Md Motiul; Haque, Md Ashraful; Huda, AK Qumrul; et al. (Bangladesh Critical Care Journal, 2021)
Objective : To determine mechanical ventilation discontinuation (weaning) practices in Bangladesh as there is currently no data available on this issue. Method : Analyzing the Survey on Bangladeshi respondents using questionnaire developed by and used by a pan Asian study where Bangladesh critical care physicians participated. Result : 40 physicians from 10 ICUs of Bangladesh participated. Majority of our participating doctors (62.5%) came from private for profit hospital. 19 out of 40 respondents were certified in critical care medicine. In our study spontaneous breathing trial (SBT) was liberally used with pressure support being used by 30% respondents. Most of the extubation trial took place during day. As criteria for extubation, respondents mainly considered consciousness and cooperation and along with gag reflex, cough strength, suction frequency and cuff leak at different times. Noninvasive ventilation (NIV) was commonly used for early extubation in cases of COPD, cardiogenic pulmonary edema, neuromuscular disorders, post-operative cases and obesity. Slightly less than half of respondents did not follow any sedation protocol and 42.5% followed weaning protocol. Protocolized weaning by nurses are not known to be practiced in Bangladesh. Conclusion : Weaning practices are diverse in Bangladeshi ICUs. Protoclized weaning is rarely practiced in Bangladesh. Bangladesh Crit Care J March 2021; 9(1): 4-11